PERTUMBUHAN PRASAPIH PEDET PERANAKAN ONGOLE DAN SIMMENTAL PERANAKAN ONGOLE JANTAN DAN BETINA YANG DIPELIHARA PADA KONDISI YANG SAMA - , HARJANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to observe the preweaning growth of Ongole Grade (PO) and Simmental-Ongole Grade Cross (SimPO) calves. This research used 4 heads of PO male, 7 heads of PO female, 15 heads of SimPO male, and 20 heads of SimPO female calves. The calves were raised with their dam prior to weaning age (90 days). The data were analyzed by completely randomized design cross classification (2x2). The average birth weight and average daily gain (ADG) of PO and SimPO calves were 26.18±3.40 and 30.11±5.60 kg, and 0.54±0.09 and 0.58±0.14 kg/head/day, respectively. The birth weight of SimPO were higher (P<0,05) than PO calves. There was no significant different ADG between PO and SimPO calves. The Average birth weight and ADG of male and female calves were 30.31±5.81 and 28.37±5.04 kg, and 0.55±0.17 and 0.57±0.10 kg/head/day, respectively. There was no significant different birth weight and ADG between male and female calves. There were no interaction between breed and sex on birth weight and ADG. There was no significant different body size gain between PO and SimPO calves as well as between male and female calves. There was no interaction between breed and sex on body size gain. It is concluded that the preweaning growth of PO and SimPO male and female calves are similar. Key words: calves, PO, SimPO, preweaning growth.